Innovation strategies, teacher development and internationalization: Key factors to organizational performance of HEIS - Antunes, Marina Godinho; Mucharreira, Pedro Ribeiro; Justino, Maria do Rosário Texeira Fernandes; Quirós, Joaquín Texeira (International Journal of Innovative Research and Scientific Studies, 2025)
The objective of this study is to evaluate the impact of innovation strategies, teacher development, and internationalization initiatives on the organizational performance of Higher Education Institutions (HEIs). Considering globalization and the evolving challenges and requirements of contemporary society, HEIs must explore new quality assurance tools to enhance their competitiveness and ensure their survival. Methodologically, a survey was conducted among members of Portuguese HEIs. To analyze the relationships between the identified variables, multiple linear regression analysis was employed. The findings reveal that specific Total Quality Management (TQM) variables, particularly those related to teacher involvement, empowerment, and training, have a notable influence on the organizational performance of HEIs. Moreover, it is important to emphasize that innovation and internationalization strategies exhibit a significant correlation with organizational performance outcomes. This research is essential for deepening the understanding of HEIs, given their critical role in national development and their contributions to knowledge generation and societal advancement. As these institutions navigate increasingly competitive environments, identifying key drivers of organizational performance is of paramount importance.